Is Salivary S100B a Biomarker of Traumatic Brain Injury? A Pilot Study - Janigro, Damir; Kawata, Keisuke; Silverman, Erika; Marchi, Nicola; Diaz-Arrastia, Ramon (Frontiers in Neurology, 2020)
Traumatic brain injury (TBI) is a common cause of short and long-term disability as well as an etiologic factor for delayed neurodegeneration. Mild traumatic brain injury (mTBI) represents up to 85% of head injuries; diagnosis and early management involves computed tomography (CT) or in-hospital observation, which are time- and cost- intensive. CT involves exposure to potentially harmful ionizing radiation and >90 % of the scans are negative. Blood-brain barrier (BBB) damage is suspected pathological event post-TBI contributing to long-term sequelae and a reliable and rapid point-of-care test to screen those who can safely forego acute head CT would be of great help in evaluating patients with an acute mTBI. We developed a test to measure salivary S100B, which has been shown, when analyzed in blood, to have an excellent negative predictive value for abnormal CT. Fifteen adult patients with suspected TBI (mean age = 47 years, range 18-79) were compared to 15 control subjects (mean age = 33 years, range 23-53). We found that average salivary S100B levels were 3.9 fold higher than blood regardless of the presence of pathology. We found that [S100B]saliva was correlated with [S100B]serum (Pearson’ coefficient=0.79; p<0.01). Salivary S100B levels were as generally effective in differentiating TBI patients from control subjects as serum levels (Control vs. TBI: p<0.01; Serum ROCAUC=0.94 and Saliva ROCAUC=0.75). In this pilot study, gender, ethnicity and age did not significantly influence salivary S100B levels. In conclusion, our results suggest that salivary S100B is a promising alternative to serum S100B in the diagnosis of TBI.